Critical Illness Myopathy and GLUT4: Significance of Insulin and Muscle Contraction - Weber-Carstens, Steffen; Schneider, Joanna; Wollersheim, Tobias; Assmann, Anke; Bierbrauer, Jeffrey; Marg, Andreas; Al Hasani, Hadi; Chadt, Alexandra; Wenzel, Katrin; Koch, Susanne; Fielitz, Jens; Kleber, Christian; et al. (American journal of respiratory and critical care medicine, 2013)
Critical illness myopathy (CIM) has no known cause and no treatment. Immobilization and impaired glucose metabolism are implicated. We assessed signal transduction in skeletal muscle of patients at risk for CIM. We also investigated the effects of evoked muscle contraction. In a prospective observational and interventional pilot study, we screened 874 mechanically ventilated patients with a sepsis-related organ-failure assessment score greater than or equal to 8 for 3 consecutive days in the first 5 days of intensive care unit stay. Thirty patients at risk for CIM underwent euglycemic-hyperinsulinemic clamp, muscle microdialysis studies, and muscle biopsies. Control subjects were healthy. In five additional patients at risk for CIM, we performed corresponding analyses after 12-day, daily, unilateral electrical muscle stimulation with the contralateral leg as control. We performed successive muscle biopsies and assessed systemic insulin sensitivity and signal transduction pathways of glucose utilization at the mRNA and protein level and glucose transporter-4 (GLUT4) localization in skeletal muscle tissue. Skeletal muscle GLUT4 was trapped at perinuclear spaces, most pronounced in patients with CIM, but resided at the sarcolemma in control subjects. Glucose metabolism was not stimulated during euglycemic-hyperinsulinergic clamp. Insulin signal transduction was competent up to p-Akt activation; however, p-adenosine monophosphate-activated protein kinase (p-AMPK) was not detectable in CIM muscle. Electrical muscle stimulation increased p-AMPK, repositioned GLUT4, locally improved glucose metabolism, and prevented type-2 fiber atrophy. Insufficient GLUT4 translocation results in decreased glucose supply in patients with CIM. Failed AMPK activation is involved. Evoked muscle contraction may prevent muscle-specific AMPK failure, restore GLUT4 disposition, and diminish protein breakdown. Clinical trial registered with http://www.controlled-trials.com (registration number ISRCTN77569430).